Analysis of ChatGPT User Acceptance Among Gen Z using UTAUT and TPB Methods - Putra, Defri Indra; Fronita, Mona; Angraini, Angraini; Megawati, Megawati (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The rapid advancement of digital technology has led to various innovations, one of which is ChatGPT—a language model powered by artificial intelligence (AI) that has gained significant popularity among younger generations, particularly Generation Z. This study aims to analyze the factors influencing the acceptance and use of ChatGPT among Gen Z by integrating two theoretical frameworks: the Unified Theory of Acceptance and Use of Technology (UTAUT) and the Theory of Planned Behavior (TPB). Based on data analysis using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) approach, the research model demonstrates strong explanatory power, with an R² value of 0.722 for behavioral intention and 0.687 for use behavior. This indicates that the variables within the model account for a substantial proportion of the variance in the intention and actual use of ChatGPT. Out of the ten hypotheses tested, only four relationships were found to be statistically significant: Perceived Behavioral Control → Behavioral Intention, Perceived Behavioral Control → Use Behavior, Habit → Behavioral Intention, and Behavioral Intention → Use Behavior. The study involved 96 Gen Z respondents residing in Pekanbaru, selected using a simple random sampling technique. Data were collected through the random distribution of questionnaires in various WhatsApp groups. The findings indicate that individual perceptions of control and habitual use play a crucial role in determining both the intention and actual behavior of using ChatGPT. In contrast, variables such as subjective norm, attitude toward behavior, performance expectancy, effort expectancy, hedonic motivation, and facilitating conditions did not show significant influence in this context. These results suggest that internal factors—particularly perceived behavioral control and user habits—are more dominant in influencing ChatGPT usage among Gen Z than external or social factors. Therefore, it is essential to design features that enhance user autonomy and promote the formation of positive usage habits.